2022
DOI: 10.2991/978-94-6463-008-4_102
|View full text |Cite
|
Sign up to set email alerts
|

Content Value Versus Influencer Credibility: What Matters More for Followers’ Trust and Behavioral Intention Towards Collaborative Brands?

Abstract: Instagram is one of the top three most popular social media platforms in Indonesia. Nowadays, many local brand owners collaborate with influencers to promote products or services sold through Instagram. This study examines the extent to which influencer credibility and advertising content value are shared to create brand trust and consumer behavioral intention. The online survey was distributed to 206 followers of three female Indonesian fashion influencers with at least four hundred thousand followers on Inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…As also hinted recently by Pambudi et al, (2022) this study found that content value and its quality positively influence users' intentions to engage with influencer and participate in social media platforms. If the content value is deemed superior from others; it will have more chances to create stronger intentions of purchase from the followers.…”
Section: Discussionsupporting
confidence: 76%
“…As also hinted recently by Pambudi et al, (2022) this study found that content value and its quality positively influence users' intentions to engage with influencer and participate in social media platforms. If the content value is deemed superior from others; it will have more chances to create stronger intentions of purchase from the followers.…”
Section: Discussionsupporting
confidence: 76%
“…Influencer credibility refers to the degree of attractiveness, trustworthiness, knowledge, and resemblance that followers acknowledge in influencers, all of which have the power to convince or affect their opinions (Pambudi et al, 2023). Studies pertaining to the credibility of social media influencers have concentrated on diverse aspects impacting the opinions of their followers (Coutinho et al, 2023;Belanche et al, 2021).…”
Section: Literature Review Influencer's Credibilitymentioning
confidence: 99%